2001
DOI: 10.1097/00003246-200102000-00009
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine reduces respiratory burst but augments neutrophil phagocytosis in intensive care unit patients

Abstract: These findings suggest that infusion of NAC in high doses affects granulocyte functions in critically ill patients. Antimicrobial host defense requires the effective sequence of cell adhesion, phagocytosis, and bactericidal respiratory burst. The enhanced phagocytotic activity might be a compensatory mechanism in states of impaired respiratory burst to maintain tissue sterility. For certain mechanisms of disease, the effects observed might be favorable (e.g., ischemia/reperfusion, endothelial cell activation),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 30 publications
1
64
0
6
Order By: Relevance
“…the production of reactive oxygen species, is an important defense mechanism by which phagocytes destroy micro-organisms (22)(23)(24). In a rat model of IgG immune complex-induced lung injury, reactive oxygen species may explain early induction of lung injury (within 30 min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the production of reactive oxygen species, is an important defense mechanism by which phagocytes destroy micro-organisms (22)(23)(24). In a rat model of IgG immune complex-induced lung injury, reactive oxygen species may explain early induction of lung injury (within 30 min).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it slightly but significantly increased TCC formation to 36 MFI (23-66; p Ͻ 0.05). No change in TCC formation was seen for the isotype-matched control antibody [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]]. …”
mentioning
confidence: 99%
“…Plasma REDST was previously shown to be correlated with the intracellular glutathione redox state, at least in some tissues, 26 and NAC treatment was previously shown to cause a decrease in the production of superoxide anion by stimulated neutrophils. [27][28][29][30] In view of recent evidence for a role of nitrosothiols in regulating the ventilatory response at the level of the nucleus tractus solitarius, 23 there is also the possibility that oral NAC application or the endogenous concentration of thiols or REDST may modulate HVR by altering nitric oxide production. and after 4 days of treatment (day 5) and the data on day 6 before, during, and after a 6-hour exposure to prolonged hypoxia indicated by the windows.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine has been extensively studied in critically ill patients with acute respiratory distress syndrome, organ failure, and septic shock. These studies have produced inconsistent results [83,89,90]. Crimi et al [83] suggested that larger trials in specific populations of critically ill patients in which Nacetylcysteine is administered early could potentially provide some beneficial effects.…”
Section: Antioxidant Nutrients In Neurocritical Carementioning
confidence: 99%